2013
DOI: 10.7124/bc.000813
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral properties of herbal flavonoids – inhibitors of the DNA and RNA synthesis

Abstract: Aim. To investigate influence of the Deschampsia caespitosa L. and Calamagrostis epogeios L. herbal extract (HE) and its main components – quercetin derivatives – on the DNA and RNA synthesis; to per- form comparative analysis of their antiviral activities. Methods. The model transcription system of bacteriophage T7 (RNAP T7) and polymerase chain reaction (PCR) were used as test systems. For antiviral studies there were employed models of influenzal and herpetic infections and hepatitis C. Results. It was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
2
8
0
3
Order By: Relevance
“…Therefore, both RNA synthesis catalyzed by T7 RNA polymerase and synthesis of DNA fragments by Taq polymerase were sensitive to the inhibition by ellagitannin extract in concentration-dependent mode. The inhibitory concentrations in cellfree system were of the same order of magnitude as those found for several flavonoid substances assayed in our previous work [18] that provided good reason for assessing ellagitannins under study as antiviral substances in the specific system of HIV-producing cells.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, both RNA synthesis catalyzed by T7 RNA polymerase and synthesis of DNA fragments by Taq polymerase were sensitive to the inhibition by ellagitannin extract in concentration-dependent mode. The inhibitory concentrations in cellfree system were of the same order of magnitude as those found for several flavonoid substances assayed in our previous work [18] that provided good reason for assessing ellagitannins under study as antiviral substances in the specific system of HIV-producing cells.…”
Section: Resultssupporting
confidence: 77%
“…The previous studies suggested that the combination of several non-eukaryotic polymerase systems may be useful as the primary screening tool for antiviral substances of different classes of natural and synthetic compounds [17]. Earlier, this system was successfully used in the screening of several herbal flavonoids as the putative antiviral agents [18]. Later on, we confirmed their anti-HIV activity in specific assays [19].…”
Section: Introductionmentioning
confidence: 60%
“…В світовій літературі є багато публікацій щодо протимікробних, противірусних, апоптоз-та імуномодулюючих властивостей речовин, отриманих із вищих рослин, токсинів членистоногих та гідробіонтів [12][13][14][15][16]. Препарат Протефлазид, розроблений НВК «Екофарм» (Україна), містить карбонові кислоти та флавоноїдні глікозиди, виділені з диких злаків Deschampsia caespitosa L. (щучка дерниста) та Сalamagrostis epigeios L. (війник наземний) [17]. З літературних джерел відомо, що флавоноїди можуть бути природними хіміопротекторами онкологічних захворювань (геністеїн, кварцетин), деякі з них мають антивірусні властивості, оскільки здатні інгібувати зворотну транскриптазу і ДНК-полімеразу вірусів (ретровіруси, герпесвіруси), можливо, вони можуть впливати і на інші ферменти вірусів та клітин.…”
unclassified
“…За даними Л.Г. Пальчиковської і співавторів [17] мішенню флавоноїдів слугують вірусні ферменти − транскриптаза і протеаза. Виявлено високу пригнічуючу активність діючої речовини препарату Протефлазид на синтез РНК in vitro в модельній транскрипційній системі бактеріофага Т7 та придушення процесу ампліфікації: значення ІС 90 , при якому діюча речовина повністю пригнічує синтез ДНК, становить 8 мкг/ мл.…”
unclassified
“…ханізм дії Протефлазіду раніше показаний, зокрема, на моделях ВІЛ-інфекції in vitro [4] та грипозної інфекції [5]. Інгібувальна активність препарату встановлена також для фагової РНК-полімерази і Taq-полімерази [6].…”
unclassified